(untitled) (Research, Society and Development, 2022)
Introduction: esophageal pathologies with histopathological changes can cause dyspeptic symptoms, retrosternal and epigastric pain. Objectives: to identify the prevalence of histopathological findings of the esophageal mucosa and to correlate with the bacterium Helicobacter pylori (HP). Methodology: cross-sectional, retrospective study, with 1,953 histopathological reports of the esophageal mucosa. Data analyzed by absolute and relative frequency, Pearson’s Chi-Square, Mann-Whitney and Chi-Square Test with Monte-Carlo simulations. Results: 1953 reports of esophageal lesions were analyzed: female gender 982 (50.3%) and median age 44. 151 (7.7%) reports were positive for HP and of these, 41 (2.3%) had gastric atrophy. Esophagitis 1427 (73.1%), metaplasia 548 (28.1%) and Barrett’s esophagus 133 (6.8%) were more prevalent. Malignancy, 5 (0.3%) reports. Of the patients with PH: esophagitis 97 (64.2%), Barrett’s esophagus 17 (11.3%) and metaplasia 45 (29.8%) - statistically significant pancreatic metaplasia (p<0.001). Two (1.3%) reports showed malignancy associated with PH. Correlating HP with esophageal lesions, there was a tendency to determine a higher risk of the presence of the bacteria: Barrett’s esophagus (RR: 1.68 (95%CI: 1.05-2.69), epithelial hyperplasia (RR: 2.18 (RR: 2.18) 95%CI: 1.18-4.02), glycogenic acanthosis (RR: 3.69 (95%CI: 2.08-6.54), polyps (RR: 2.17 (95%CI: 1.14-4, 16), malignancy (RR: 4.91 (95%CI: 1.66-14.52) and gastric atrophy (RR: 3.44 (95%CI: 2.02-5.84). Conclusion: Barrett’s esophagus, Epithelial hyperplasia, glycogenic acanthosis, polyps, malignancy and gastric atrophy are associated with an increased risk of the presence of the bacteria.